IMPLEMENTASI UNDANG-UNDANG NOMOR 16 TAHUN 2019 TENTANG PERKAWINAN (Studi Kasus Perkawinan anak di Kabupaten Bojonegoro) - Adilla Kartika Siwie; Heru Irianto; Anisa Kurniatul Azizah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2021)
Marriage is a permanent relationship between a man and a woman that isrecognized as valid by the community concerned based on the applicable marriage regulations. While child marriage is a marriage perfomed by a child who is 19 years old based on law number 16 of 2019 on marriage. Cases of marriage are very common in Bojonegoro district, where the majority of the population still thinks that marrying young is a must. Factors that affect child marriage are juvenile delinquency, lack of education, etc. This is a concern for the government, especially the Dinas for Womens Empowerment, Child Protection and Family Planning, Bojonegoro Regency and the community must help move together in preventing child marriage. From this explanation, this research examines the following problems: (1) how is the implementation of law number 16 of 2019 refarding marriage in Bojonegoro district?, (2) what factors influence the existence of child marriage ini Bojonegoro Regency?, (3) how are the efforts made by the Office to prevent child marriages based on law Number 16 of 2019 concerning marriage in Bojonegoro Regency. The purpose of this study to determine the implementation oflaw No.16 of 2019 regarding marriage in Bojonegoro Regency, to find out the factors that affect child marriage in Bojonegoro, to find out the efforts made by DP3AKB so that child marriage does not occur based on law No.16 of 2019 concerining marriage. To achieve this goal, this study uses a descriptive qualitative type of research, namely describing the phenomena that occur. Data collection was done through observational interviews and documentation. The conclusion of this study is that the Office of Woman Empowerment for Child Protection and Family Planning in Bojonegoro regency has a fairly good responsiveness both to the prevention of child marriages such as the many efforts to make child marriage prevention programs. The effectiveness of the Implementation of Law No.16 of 2019 concerning marriage carried out by the DP3AKB of Bojonegoro Regency is quite good, however it is not yet fully effective becauses of the many factors that encourage child marriage it from the people of Bojonegoro Regency.